The implementation of Task Based Language Teaching (TBLT) to improve ESL students’ fluency / Dr. Daljeet Singh Sedhu Janah Singh ... [et al.] - Janah Singh, Daljeet Singh Sedhu; Jufiza, A. Wahab; Hasbullah, Mohd Nasurudin; Mohd, Thuraiya; Bahaluddin, Azrul (Universiti Teknologi MARA, Kedah, 2024)
Of the speaking skills, fluency can be one of the most difficult to improve. However, it is often the main goal of almost every second language learner since the communicative approach is the primary focus of language learning. The Malaysian teaching context has witnessed a gradual shift from the traditional grammar-translation approach to a more communicative one, thereby making it necessary to discover new strategies to develop students’ speaking skills. This action research was conducted to explore the usage of TBLT by Malaysian ESL students to increase speaking fluency. A quasi-experimental research method was applied in the study to monitor the students' progress in speaking fluency and accuracy. The choice of respondents for the study involves selection using the Simple Random Sampling technique which involved 50 students enrolled in the first semester of classes at the Higher Learning Institution in Perak, Malaysia. Pre-tests at the start of the semester and post-tests at the end of the semester were used to gather data on the students' speaking abilities. The data was analysed quantitatively using descriptive and inferential statistics involving, mean score analysis, t-value and presented in the form of tables for univariate analysis by using SPSS. The result of the study indicates that the selfconversation recording by the students can improve the fluency with grammatical accuracy; and the achievement in the fluency of the students from the experimental group was considerably higher than the control group. The average N-gain score from the experimental group students was better than the control group students (.0424>0.205). However, the mean score achieved in the pre-test in the experimental class and control class was (52.14 <59>67.40). The paired sample t-test indicates a significant improvement with t-value of -14.237 and p. value = .000<0.005. Therefore, it was concluded that the use of TBLT applications could generate good results in the development of speech fluency in students. In the future, lecturers can use the innovation project with students during class time to improve their students’ speaking fluency.